2021
DOI: 10.1002/pol.20210365
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial ultrafiltration membrane with silver nanoparticle impregnation by interfacial polymerization for ballast water

Abstract: Interfacial polymerization technology was employed to immobilize silver (Ag) nanoparticles on the surface of commercial polyethersulfone (PES) membrane to develop antibacterial and antifouling ultrafiltration membrane. Ag nanoparticles were prepared from the reduction of silver nitrate (AgNO3) by sodium borohydride in the presence of polyethyleneimine (PEI) as the stabilizer. The encapsulated Ag nanoparticles in the PEI solution were embedded into the PEI membrane when trimesoyl chloride solution was used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The antibacterial activity of the material was analyzed using the platelet antibacterial method and oscillation method. The antibacterial rate could be calculated according to Equation () to compare the antibacterial activity of the composite membrane 7 P=AB/A P is the antibacterial rate (%); A is the number of colonies in the blank control; B is the number of colonies in the composite membrane with different Ag contents.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antibacterial activity of the material was analyzed using the platelet antibacterial method and oscillation method. The antibacterial rate could be calculated according to Equation () to compare the antibacterial activity of the composite membrane 7 P=AB/A P is the antibacterial rate (%); A is the number of colonies in the blank control; B is the number of colonies in the composite membrane with different Ag contents.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of antibacterial agents has proven to be an effective method for enhancing antibacterial properties. Due to their excellent antibacterial activity and high safety, the deposition of Ag NPs on filter materials has great potential for application as antibacterial protection materials 7,8 . Wu et al prepared polylactide (PLA) nanofiber membranes containing Ag NPs and tea polyphenol (TP) by electrospinning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Another study also reported the incorporation of AgNPs into polyamide 12 membranes that were obtained by the selective laser sintering method that was followed by washing, pretreatment, and functionalization with alkoxides and silanes. 47 More studies that report the use of AgNPs in polymeric membranes include the incorporation into poly(ether sulfone) membranes to develop antibacterial and antifouling ultrafiltration membranes 48 and into polysulfone ultrafiltration membranes among others. 49 Zinc oxide (ZnO) nanoparticles have also been used expansively as cheap, ecological, and hydrophilic materials since they not only provide antifouling properties to the composite membranes but also provide a photocatalytic self-cleaning capability.…”
Section: Nanoparticle-based Polymericmentioning
confidence: 99%
“…Aside from GO, Ag NPs have also risen in popularity due to their antibacterial properties. To develop antibacterial and antifouling properties, Zhu and Lua [ 43 ] employed interfacial polymerization to bind Ag NPs on the surface of an industrial PES membrane. Sprick [ 44 ] also developed a method for chemically immobilizing Ag NPs onto membranes without compromising the antimicrobial properties of the Ag NPs.…”
Section: Introductionmentioning
confidence: 99%